Risk factors for central venous catheter‐related infections in a neonatal population - systematic review - Viviane Rosado; Paulo A.M. Camargos; Lêni M. Anchieta; Maria C.F. Bouzada; Gabriela M. de Oliveira; Wanessa T. Clemente; Roberta M. de C. Romanelli (Brazilian Society of Pediatrics, 2018)
Objective: This was a systematic review of the incidence density and risk factors for central venous catheter‐related infections in a neonatal population. Data source: The MEDLINE, Embase, Cochrane, BDENF, SciELO, and LILACS databases were used without date or language restriction. Studies that analyzed risk factors for bloodstream infections in newborns were identified. Data synthesis: A total of 134 articles were found that met the eligibility criteria. Of these articles, 14 were selected that addressed risk factors for central venous catheter‐related infection in neonates. Catheter‐related bloodstream infections remain an important complication, as shown by the incidence rates reported in the studies included in this review. The observed risk factors indicate that low birth weight, prematurity, and longer catheter permanence are related to a higher incidence of bloodstream infections. It has been observed that low rates of catheter‐related infections, i.e., close to zero, are already a reality in health institutions in developed countries, since they use infection surveillance and control programs. Conclusion: Catheter‐related bloodstream infections still show high incidence density rates in developing countries. The authors emphasize the need for further longitudinal studies and the need for better strategies to prevent risk factors, aiming at the reduction of catheter‐related infections.